2011
DOI: 10.1111/j.1365-2222.2011.03738.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of intestinal dendritic cells subsets in the establishment of food allergy

Abstract: Sensitization to PE in this mouse model was accompanied by a shift in DC subsets in intestinal tissues towards more CD11b(+) DC and less CD103(+) DC. No significant changes in the plasmacytoid DC (pDC) numbers were observed. Flt3L treatment, resulting in the expansion of all DC subtypes, inhibited allergic manifestations in our model, including Th2 cytokine production, PE-specific IgE and PE-induced mast cell degranulation. pDC depletion reversed Flt3L-induced inhibition of IgE responses and mast cell degranul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 32 publications
1
49
0
2
Order By: Relevance
“…Increased numbers of CD11b+ DCs and decreased numbers of CD103+ DCs were observed after sensitization with peanut allergens in a mouse peanut allergy model [14]. Tolerogenic CD103+ DCs are known for their different migratory capacity (homing to mesenteric lymph node; MLN) and capacity to induce peripheral tolerance by inducing FoxP3+ CD4+ Tregs [1,5,15].…”
Section: Introductionmentioning
confidence: 99%
“…Increased numbers of CD11b+ DCs and decreased numbers of CD103+ DCs were observed after sensitization with peanut allergens in a mouse peanut allergy model [14]. Tolerogenic CD103+ DCs are known for their different migratory capacity (homing to mesenteric lymph node; MLN) and capacity to induce peripheral tolerance by inducing FoxP3+ CD4+ Tregs [1,5,15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, OX40L on this DC subset Allergic Sensitization to Foods seemed to be selectively responsible for the allergic sensitization component of the adjuvant activity of CT. 40 Within the lamina propria it has been found that allergic sensitization is associated with an expansion of CD11b 1 DCs and a relative reduction of CD103 1 DCs. 41 These data indicate that the phenotype of the gastrointestinal DC determines the outcome of sensitization versus tolerance to foods.…”
Section: Mechanism Of Action Of Adjuvantsmentioning
confidence: 96%
“…Одновременное введение токсинов бактери-ального происхождения с антигенами влияет на экспрес-сию рецепторов главного комплекса гистосовместимо-сти (MHC II) и костимуляторных молекул на дендритных клетках и индуцирует T х2 -ответ с повышением продукции ИЛ 4 и интенсификацией синтеза антигенспецифиче-ских IgE и IgG 2a [50,51]. В экспериментальных исследо-ваниях показано, что воздействие холерных токсинов индуцирует аллергическую сенсибилизацию к экстракту арахиса, вызывая сдвиг подвидов дендритных клеток в собственной пластинке и пейеровых бляшках с более провоспалительных CD11b(+) на менее толерогенные CD103(+) клетки [52]. Более того, обнаружена повышен-ная экспрессия Т-клеточной (иммуноглобулин и муцин) доменовой молекулы (TIM-4) в дендритных клетках кост-ного мозга мышей после конкурентного воздействия холерных токсинов и аллергенов арахиса по сравнению с таковыми, обработанными только одними аллергенами [53].…”
Section: кишечная микрофлора и оральная толерантностьunclassified